The Role of Elderly Posyandu in Improving Elderly Welfare in Alai Village - Nadila; Vina Oktaviani; Sri Wahyuni (PT FORMOSA CENDEKIA GLOBAL, 2022)
Elderly Posyandu is an integrated service post for people who are elderly in a certain area, which in this case has been agreed upon and driven by the community whereby they can get health services. This research uses qualitative research methods, with collection techniques. data, observation, interview and documentation. The results of the research conducted show that the role of the elderly Posyandu in Alai Village, Ungar District, Karimun Regency is still experiencing problems, namely the lack of community participation, especially among the elderly and the limited space for the elderly Posyandu activities to be carried out.